A Bioinspired Triple‐Hierarchical Superhydrophobic Surface with Exceptional Robustness to Water Impingement. Issue 3 (2nd February 2023) - Chung, Soochan; Riley, Cameron; Taylor, Hayden
Abstract : An SEM image of a triple‐hierarchical superhydrophobic surface (TriSS) inspired by water‐repellent lotus leaves, which consist of arrays of microprotrusions with various sizes, grooves between the protrusions, and a covering of nanoscale hairs. The TriSS surface achieves an exceptional repellence to water via the extremely limited liquid–solid contact area enabled by the distinctive artificial three‐tier surface roughness. Further details can be found in the article number 2201315 by Hayden Taylor and co‐workers.